Implementation of Web-Based Counseling System at SMK Negeri 1 Sukawati - Welda, Welda; Kusuma, Aniek Suryanti; Junantara, Argi (INFOTEKS (Information Technology, Computer and Sciences), 2025)
State Vocational High School (SMK) Negeri 1 Sukawati, located in Gianyar Regency and renowned for its excellence in the field of visual arts, had a total of 533 students in the 2023/2024 academic year. As part of its efforts to enhance the quality of education, the school has implemented a Guidance and Counseling (BK) program aimed at helping students develop self-awareness, improve self-confidence, and behave in accordance with school regulations. One of the key components of this program is the student violation recording system. Currently, the process of recording violations is carried out manually using BK logbooks and Microsoft Excel, which is time-consuming and requires a high level of accuracy. This becomes a significant challenge considering the large number of students and the variety of infractions that need to be documented. This study aims to design and implement a web-based guidance and counseling information system to facilitate a more efficient and accurate method of recording student violations. By utilizing a web-based system, the recording process can be automated, data retrieval becomes easier, and student or parental summons can be generated automatically once certain violation thresholds are reached. The focus of this research is the development of a system that enables guidance counselors to report student violations more easily, contributing to improved student discipline. The implementation of this system is expected to enhance the efficiency of violation data management and support the school’s efforts in fostering better student discipline.